Chronic hereditary pancreatitis with N29I mutation in a Turkish child - Eren, Makbule; Gürakan, Figen; Koçak, Nurten (The Turkish Journal of Pediatrics, 2005)
Hereditary pancreatitis, an autosomal dominant disease, is the second most common cause of pancreatitis in children. Here we report a child with recurrent pancreatitis attacks and N29I mutation. Due to the increased risk of pancreatic cancer, taking a detailed past and family history and early diagnosis are important.